Casual Style in Steve Harvey Show: A Socio linguistic Perspective - Hameed Ma youf, Hussain (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to investigate the use of casual style in the Steve Harvey Show. To achieve this aim, the data is analyzed socio-linguistically. It is hypothesized that casual style is the dominant style in the show. The procedure adopted is to survey the concept of style, types of style, and functions of style theoretically. Among the important conclusions that the study comes up with are: The appearance of casual style in the show is quite clear. Casual style is the dominant style of the show.